2008
DOI: 10.1002/asi.20858
|View full text |Cite
|
Sign up to set email alerts
|

Components of abstracts: Logical structure of scholarly abstracts in pharmacology, sociology, and linguistics and literature

Abstract: The international standard ISO 214:1976 defines an abstract as "an abbreviated, accurate representation of the contents of a document" (p. 1) that should "enable readers to identify the basic content of a document quickly and accurately to determine relevance" (p. 1). It also should be useful in computerized searching.The ISO standard suggests including the following elements: purpose, methods, results, and conclusions. Researchers have often challenged this structure and found that different disciplines and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Notwithstanding a lack of consensus among scholars concerning a standard pattern in abstract writing (Martín 2003;Phuong Dzung 2008;Sauperl et al 2008, Loan et al 2014, Chan & Ebrahimi, 2012, the IMRD structure as an academic norm, however, is accepted as a standard pattern approved by most researchers because the structure apparently satisfies the ISO 214 and American National Standard definitions (Lores 2004). Moreover, Swales (1990) also highlights the format of the abstract as having Introduction, Method, Results and Discussion (IMRD) structure which is similar to that of the main article.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding a lack of consensus among scholars concerning a standard pattern in abstract writing (Martín 2003;Phuong Dzung 2008;Sauperl et al 2008, Loan et al 2014, Chan & Ebrahimi, 2012, the IMRD structure as an academic norm, however, is accepted as a standard pattern approved by most researchers because the structure apparently satisfies the ISO 214 and American National Standard definitions (Lores 2004). Moreover, Swales (1990) also highlights the format of the abstract as having Introduction, Method, Results and Discussion (IMRD) structure which is similar to that of the main article.…”
Section: Introductionmentioning
confidence: 99%
“…Applied linguists (e.g., Hyland, 2004; Salager‐Meyer, 1991; Swales, 1990; Tibbo, 1992) have studied in detail the move structure and verb tense usage of abstracts in scientific research papers. Researchers from different countries and linguistic backgrounds (e.g., Martin Martin, 2003; Sauperl, Klasinc & Luzar, 2008) have found that authors in these situations prefer different sequences or forms of wording for abstracts. It is commonly stated that abstracts are difficult to write but it is also argued that they should be easy to understand for both native and non‐native speakers of English (APA, 2001, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Se tomó como marco de referencia el esquema de Introducción (I), Método (M), Resultados (R) y Conclusiones/ Recomendaciones (C), frecuentemente aceptado, adecuado, sobre todo, si se utiliza con flexibilidad (Blanco, 2017(Blanco, , 2013Hyland, 2000) el cual incluye los componentes centrales de cualquier investigación. Dicho esquema ha sido a veces cuestionado (Sauperl, Klasinc & Luzar, 2008), pero aquí se sostiene que el resumen concebido de tal manera cuatripartita es utilizable dentro del marco de la cultura occidental, a la que pertenece América del Sur. Además, no es más que un tipo ideal que, como tal, no siempre mostrará una manifestación pura y total del fenómeno, sino que es una noción simplificada de él, con base en rasgos que pueden ser difusos, discretos, más o menos presentes y ocasionalmente ausentes (Lengermann, 1974).…”
Section: Métodounclassified